Persepsi Orang Tua terhadap Pemberian Imunisasi MR pada Anak Sekolah Dasar Berbasis Agama - Muhammad Harli; Bagoes Widjanarko; Farid Agushybana (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2019)
Background: MR immunization campaign is a national strategy to eliminate measles and rubella in 2020. Musi Rawas district have experienced clinical measles outbreaks in the last 3 years. There were many rejections happened during MR mass immunization implementation. Megang Sakti Subdistrict is one of the sub-district with high rate of rejection from parents of the students at religious-based elementary school. This research aims to identify parents’ perceptions on MR immunization program for elementary school students based on health belief model theory.Method: This study employs quantitative research with cross sectional approach. The subject of the study were 100 parents of the grade 1-6 students at religious-based elementary school at Megang Sakti sub-district. The sample was selected using simple random sampling. Structured questionnaires were used that have been validated in other subdistrict priorly. Data was analysed by using univariate, Chi-Square and multiple logistic regression for analysis.Results: The results show that 21% of parents have rejected their children to be immunized MR (Measles Rubella). Perceived susceptibility and severity variables have not significantly associated to parent’s rejection. However, perceived benefits and barriers have significantly influenced to the rejection. The biggest barrier in immunizing MR for their children was the parent’s believed that the immunization vaccine substances were not halal refers to Islamic rules. The study suggests that the government should provide comprehensive information related to vaccines’ substances so that people do not hesitate to receive immunization of their children.